Implementasi Manajemen dalam Pengelolaan Sekolah/Madrasah - Dedik Dedik; Chadiza Auliana Utami; Aulia Asmidah Hsb; Shintia Agustina (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Education is the primary foundation for developing competitive and high-quality human resources; therefore, the management of educational institutions such as schools and madrasahs requires a structured, efficient, and quality-oriented management system. This study aims to examine the implementation of management in the administration of schools/madrasahs, covering the basic concepts of educational management, the role of school principals, stages of implementation, and related strategies. A descriptive qualitative approach was used, with data collected through literature studies from various academic sources. The results show that effective educational management includes an integrated process of planning, organizing, implementing, and supervising all educational resources. The school principal plays a central role as a transformational leader who directs the vision and success of the institution. The implementation process includes stages of socialization, piloting, and dissemination, while the strategies involve school categorization, phased programs, and regulatory strengthening. This entire managerial process is essential in building adaptive, accountable, and high-quality educational institutions.